Health Education to Improve the Knowledge and Attitudes of Type 2 Diabetes Mellitus Patients - Anggy Utama Putri; Dela Citra Nabela; Bella Alinggawati; Putri Handayani; Dian Ayu Pratiwi; Sintia Wati; Bobby Fernando; Bias Sandi Permadi; Novita Sari; Eva Dwi Yanti; Rofif Frari Agrahi (Abdimas Polsaka, 2026)
Type 2 Diabetes Mellitus (T2DM) is a major non-communicable disease that continues to increase globally and poses significant challenges to public health, particularly in developing countries. One of the main obstacles in T2DM management is inadequate patient knowledge and suboptimal attitudes toward disease control and self-care. This community service program aimed to improve the knowledge and attitudes of patients with T2DM through a structured health education intervention combined with physical activity promotion. The program was implemented using a pre-test and post-test design involving patients with T2DM at a primary healthcare clinic. Educational activities included interactive lectures, discussions, visual media, and guidance on simple and safe physical exercises appropriate for participants’ conditions. Patient knowledge and attitudes were assessed before and after the intervention using structured questionnaires. The results demonstrated a significant improvement in patients’ knowledge, with the mean score increasing from 11.5 in the pre-test to 15.9 in the post-test (p = 0.000). In addition, most participants showed positive attitudes toward healthy lifestyle behaviors related to diabetes management. These findings indicate that health education combined with physical activity promotion is effective in enhancing patients’ understanding and supporting positive attitudes toward self-management of T2DM. Integrating regular and structured educational programs into primary healthcare services is recommended to improve long-term diabetes management and prevent complications